Investigating the Influence of Social Class on Consumers’ Shopping Behaviour in Nigeria - Chinwendu, Okonkwo Deborah; Shedrack, Moguluwa Chinwuba (International Journal of Marketing Research Innovation, 2018)
Purpose - This research is a critical effort towards investigating the shopping behaviour of consumers among different social class categories in Nigeria. The purpose of this paper is to evaluate the underlying factors influencing consumers’ shopping behaviour in order to establish if there is really a clear-cut distinction in this regard among the various social class categories.Design/methodology/approach - This study adopted the cross-sectional research approach and the survey research method. This study was carried out in order to determine whether there is a significant influence of social class on consumers’ choice of shopping outlet; and investigate the extent to which social class significantly influenced consumers’ organization of purchases, shopping style, and shopping pattern in Nigeria. A total of 384 copies of the questionnaire were distributed to individuals within Enugu metropolis, however only 350 copies were considered usable for data analysis. Respondents were selected using the convenience sampling technique. Descriptive statistical methods such as frequencies and percentages were used in data presentation. The chi-square and multiple regression statistics were used to analyse data.Findings - The results indicate that social class significantly influenced consumers’ choice of shopping outlet; social class did not in any way significantly influence consumers’ organization of purchases; occupation/profession did not have a significant influence on consumers’ behaviour with respect to their shopping style; and income and  occupation/profession did not have a significant influence on consumers’ behaviour with respect to their shopping pattern.Practical implications – This paper presents a spotlight on Nigerian consumers’ shopping pattern vis-à-vis the age long social class theory. It revisits the significance of the concept of social class to marketing practice with a strong emphasis on consumer behaviour.Originality/Value – The significance of this paper is apparent in its proven application of the age-long social class concept in understanding consumer behaviour patterns in these contemporary times. As such, it requires a re-visit by marketing scholars so as to bring it back to limelight considering its relevance to consumer behaviourial patterns.